Active Movement: Journal of Sports Education and Physical Health - Amalia Tasya (PT. Anagata Sembagi Education, 2024)
In this modern era, attention to physical health and sports education is increasing, along with global and local health phenomena. Adequate physical activity has been shown to have a positive impact on physical and mental health, especially among children and adolescents. According to data from the World Health Organization (WHO), about 80% of adolescents worldwide are physically inactive, potentially causing long-term health problems. This study aims to explore effective sports education interventions to increase student participation. Through descriptive and correlational quantitative methods, data were collected from 300 students from various primary and secondary schools. The results showed that 70% of the students actively participated in physical activity, with significant differences between boys and girls. Parental support, accessibility of sports facilities, and social context contribute to student participation. Research by Liu and Zhao (2020) and Smith et al. (2020) supports the importance of structured sports programs and teacher training. In addition, extracurricular activities and technology can increase students' interest in sports. This research underscores the need for a holistic approach to sports education that supports students' physical and mental health, with adequate policy support. These findings are expected to make a significant contribution to the development of sports education policies and practices, as well as create an environment that supports physical activity among the younger generation